2015
DOI: 10.1105/tpc.15.00949
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Proteins RZ-1B and RZ-1C Play Critical Roles in Regulating Pre-mRNA Splicing and Gene Expression during Development in Arabidopsis

Abstract: Nuclear-localized RNA binding proteins are involved in various aspects of RNA metabolism, which in turn modulates gene expression. However, the functions of nuclear-localized RNA binding proteins in plants are poorly understood. Here, we report the functions of two proteins containing RNA recognition motifs, RZ-1B and RZ-1C, in Arabidopsis thaliana. RZ-1B and RZ-1C were localized to nuclear speckles and interacted with a spectrum of serine/arginine-rich (SR) proteins through their C termini. RZ-1C preferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 64 publications
4
78
0
Order By: Relevance
“…It was known that the RRM domain(s) of SR proteins have the ability to bind to the target pre-mRNA, and preferentially to specific RNA sequences [87,8991]. We found that SCL30 binds to the AGAAGA motif, in comparison to previous studies showed that the GAAG repeats function as the splicing enhancers [9294] in animals, and RZ-1C and SR45 proteins bind to the AG-riched motif in plant [66,95], suggesting that the AG-rich sequence might play conservative and important role in splicing both in plant and animals. It was known that most exons are bound by at least one SR protein [87,91,96,97], we thought SR45 and SC35/SCL proteins may bind to specific motifs to play redundant and cooperative roles in splicing.…”
Section: Discussionmentioning
confidence: 60%
“…It was known that the RRM domain(s) of SR proteins have the ability to bind to the target pre-mRNA, and preferentially to specific RNA sequences [87,8991]. We found that SCL30 binds to the AGAAGA motif, in comparison to previous studies showed that the GAAG repeats function as the splicing enhancers [9294] in animals, and RZ-1C and SR45 proteins bind to the AG-riched motif in plant [66,95], suggesting that the AG-rich sequence might play conservative and important role in splicing both in plant and animals. It was known that most exons are bound by at least one SR protein [87,91,96,97], we thought SR45 and SC35/SCL proteins may bind to specific motifs to play redundant and cooperative roles in splicing.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, other examples of mutations of RBPs resulted in global changes to the transcriptome. This includes a 14-day old mutant in two RNA recognition motif proteins, RZ-1B and RZ-1C, that had 3,176 DEGs (difference > 1.5-fold, P < 0.01) compared to wild-type (Wu et al, 2016). By contrast, much smaller changes to the alba456 transcriptome were observed; only 1.6% of the alba456 transcriptome were DEGs at the 2-fold change cutoff (or 0.05% at the 5-fold change cutoff) and there were very few DSGs (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Arabidopsis demonstrate widespread AS regulatory functions for the hnRNP proteins GLY-RICH PROTEIN7 (GRP7) and GRP8 (Streitner et al, 2012), POLYPYRIMIDINE TRACT BINDING PROTEIN1 (PTB1) and PTB2 , RZ-1B/RZ-1C (Wu et al, 2016), and the SR-like protein SR45 (Carvalho et al, 2016). Furthermore, binding motifs required for AS control by SR45 (Day et al, 2012) and the SC35-LIKE33 (SCL33; Thomas et al, 2012) have been identified in single target premRNAs.…”
mentioning
confidence: 99%